Sobre o projeto de paz kantiano : um fundamento filosófico do direito internacional - Campos, Nasla Rodrigues Gonçalves de Sabóia (2016)
This research aims to investigate the Kantian Project Toward Perpetual Peace from the historical French Revolution since this applicability now days. In Kant`s conception, Perpetual Peace is a unattainable ideal, but the fundamental principles are historically possible. Similar to individuals, States in their mutual relations should enter into a juridical condition. The problems about violence will not be resolved unless the establishment of an international and cosmopolitan laws. Kant alerts that each State should became a Republic, because in the republicanism the decision about get in a war is a prerogative of the citizens. They will be never be forced to go war. The citizens chose Peace because they don`t want to lose their life, liberty and rights. In a cosmopolitan law, the respect to the right of every one around the planet will assure people. This research concerning to investigates even the presumptions of the individuals emancipation on a Republic such as the emancipation of States on a Federation.